2017
DOI: 10.1166/asl.2017.9114
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Lactoferrin and Lactoperoxidase from the Colostrum of Indonesian Ettawa Crossbred Goat

Abstract: Background: Lactoferrin is a glycoprotein of the transferrin family which has multifunctional properties and useful for clinical and commercial application. It has some advantages as an immune system modulation, antibacterial activity and antioxidant in infant and adult as well as in animal. Lactoperoxidase is one of the most prominent enzymes in milk and catalyzes the inactivation of a wide range of microorganisms. Both lactoferrin and lactoperoxidase are expressed in most biological fluids, including colostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
0
1
Order By: Relevance
“…The solvent used for CAL extraction did not significantly affect (p>0.05) SG of the milk. The average SG of the milk samples was 1.0288, which is a little bit lower than the value reported by Harjanti et al (2017) at one day post-partum (1.041) and two days post-partum (1.034) for EC goats. While Tesfay et al (2015) reported that the SG of pasteurized milk was 1.031 and SG of milk taken from a vendor was 1.025.…”
Section: Milk Yield and Qualitycontrasting
confidence: 60%
“…The solvent used for CAL extraction did not significantly affect (p>0.05) SG of the milk. The average SG of the milk samples was 1.0288, which is a little bit lower than the value reported by Harjanti et al (2017) at one day post-partum (1.041) and two days post-partum (1.034) for EC goats. While Tesfay et al (2015) reported that the SG of pasteurized milk was 1.031 and SG of milk taken from a vendor was 1.025.…”
Section: Milk Yield and Qualitycontrasting
confidence: 60%